A Nomogram Based on Circulating CD4+ T Lymphocytes and Lactate Dehydrogenase to Predict Distant Metastasis in Patients with Nasopharyngeal Carcinoma - Shen D; Yan C; Chen K; Li L; Qu S; Zhu X (Dove Medical Press, 2021)
De-song Shen,1,* Chang Yan,1,* Kai-hua Chen,1 Ling Li,1 Song Qu,1 Xiao-dong Zhu1,2 1Department of Radiation Oncology, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, 530021, People's Republic of China; 2Department of Oncology, Wuming Hospital of Guangxi Medical University, Nanning, Guangxi, 530199, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiao-dong Zhu Tel +86 771 533 1466Email zhuxdonggxmu@126.comPurpose: Distant metastasis is the main pattern of treatment failure in nasopharyngeal carcinoma (NPC) in the era of intensity-modulated radiotherapy (IMRT). We aimed to establish and validate a prognostic nomogram to identify patients with a high risk of distant metastasis.Patients and Methods: A total of 503 patients with nonmetastatic NPC were included in this retrospective study. We established a prognostic nomogram for distant metastasis-free survival (DMFS) based on the Cox proportional hazards model. The predictive discriminative ability and accuracy of the nomogram were assessed with the concordance index (C-index), receiver operating characteristic (ROC) curve, and calibration curve. The nomogram's clinical utility was also evaluated using decision curve analysis (DCA) and Kaplan-Meier method. The predictive ability of the nomogram was validated in an independent cohort.Results: The multivariate analysis showed that circulating CD4+ T lymphocytes, lactate dehydrogenase (LDH), serum ferritin (SF), and N stage were independent prognostic factors for DMFS. Then, we constructed the nomogram based on these factors. The C-indexes of the nomogram for distant metastasis were 0.763 (95% CI: 0.685- 0.841) and 0.760 (95% CI: 0.643- 0.877) in the training cohort and validation cohort, respectively, which was higher than the 8th TNM staging system (0.672 and 0.677). The calibration curve showed that the prediction results of the nomogram were in high agreement with the actual observation. The ROC curve indicated that the nomogram had a better predictive ability than TNM staging. The DCA also demonstrated that the nomogram was clinically beneficial. In addition, the patients were classified into two different risk groups (high-risk, low-risk) by the nomogram.Conclusion: As a supplement to TNM staging, our nomogram could provide a more effective and accurate prognostic prediction of distant metastasis in NPC patients. It has the potential to guide the individualized treatment of patients to improve their survival.Keywords: nasopharyngeal carcinoma, nomogram, distant metastasis, CD4+ T lymphocytes, lactate dehydrogenase, prognosis